Pigmented radish (Raphanus sativus): Genetic variability, heritability and interrelationships of total phenolics, anthocyanins and antioxidant activity - SINGH, B K; KOLEY, T K; KARMAKAR, PRADIP; TRIPATHI, AJAY; SINGH, BIJENDRA; SINGH, MAJOR (The Indian Journal of Agricultural Sciences, 2017)
Radish (Raphanus sativus L.) is an important salad vegetable grown and consumed throughout the world for fleshy roots which has numerous categories' varying in root colour, size, shape and flavour. The uses of coloured radishes in the salads and their anthocyanins as colourants are gaining popularity because of the colour characteristics, health benefits as well as antioxidant activities. However, information on the genetic variability, heritability and inter-relationship of total phenolics, anthocyanins and antioxidant activities in pigmented radish is very limited, but pre-requisite to initiate breeding programme; and therefore investigated in the present study. Radish genotypes were significantly diverse for all the antioxidants; differed by 4.98-fold for total phenolics, 36.16-fold for anthocyanins content, 4.96-fold for FRAP activity and 4.03-fold for CUPRAC activity; and the genotypes accounted for >97% of total variations. The meager differences between phenotypic and genotypic coefficient of variation reveals the greater role of genotypes and lesser influence of the environment on the biosynthesis and accumulation of antioxidants. Significantly positive correlations along with higher magnitude for anthocyanins content, total phenolics, FRAP activity and CUPRAC activity (r= 0.823 to 0.964) could be used as indirect selection criteria for improving levels of antioxidant compounds. The estimates of heritability and genetic advance indicate the role of additive and non-additive genes for biosynthesis of antioxidants and root development, respectively; therefore, recurrent selection would be the best breeding approach to improve both the traits simultaneously in coloured radish.